HUNGARIAN HEROES OF AMERICAN REVOLUTIONS: THE PARTICIPATION OF HUNGARIAN IMMIGRANTS IN THE WAR FOR INDEPENDENCE AND THE CIVIL WAR IN THE USA - Tatiana V. Pantyukhina (Вестник Северо-Кавказского федерального университета)
The article deals with the role of immigrants from Hungary in the War for Independence and Civil war in the USA in the XVIII-XIX centuries. Its focus is on the remarkable contribution of Hungarian revolutionaries of «Koshuth immigration» of 1848 into the victory of the North in the war in 1861-1865.